PENGARUH LIKUIDITAS TERHADAP PROFITABILITAS PADA KOPERASI DI KABUPATEN BENGKALIS - Andryani, Gusti; Makhdalena, Makhdalena; RM. Riadi, RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study is to find out and analyze the effect of liquidity on profitability. The population and this research are active UMKM cooperatives in Bengkalis Regency which amount to 15 cooperatives. The type of data from this study is secondary data obtained from the Bengkalis District Cooperative Cooperative Office with documentation techniques. The data analysis technique from this study was to use regression with the help of SPSS. The results showed that liquidity had an effect on profitability of 57.8%.Key Words: Liquidity, Profitability